Low parental income level is associated with pediatric COVID-19 vaccine hesitancy in the San Francisco Bay area - Overbeck Christian Takou Mbah; Sara H. Goodman; Yvonne Maldonado; Jennifer Bollyky (BMC Public Health, 2025)
Abstract Objective To characterize the differences between COVID-19 vaccine-hesitant and vaccine-accepting parents in the Bay Area. Methods We analyzed a cross-sectional survey of 251 parents of children (< 18 years) from six San Francisco Bay Area counties in November of 2022. We adapted WHO’s Vaccine Hesitancy Scale (VHS) into a 9-item Likert scale measuring COVID-19 vaccine hesitancy. We assigned a VHS score to each participant, with lower VHS scores indicating higher vaccine hesitancy. We performed multiple linear regression analyses with VHS scores and children’s vaccination status as outcomes and demographic factors as predictors. Results Parents of children who had received at least one dose of the COVID-19 vaccine had a 17.1% higher VHS score compared to parents of children who had not received any dose (p < 0.01). Additionally, parents with annual income <$50,000 had a 9.6% lower VHS score compared to parents with income > $150,000 (p < 0.01), indicating higher vaccine hesitancy in lower-income parents. Conclusions Low-income parents appear to be more vaccine-hesitant than high-income parents in the Bay Area. Future public health interventions should focus on lower-income parents to improve vaccine uptake.